Modeling the impacts of biomass burning on air quality in and around Mexico City - W. Lei; G. Li; L. T. Molina (Atmospheric Chemistry and Physics, 2013)
The local and regional impacts of open fires and trash burning on ground-level ozone (O3) and fine carbonaceous aerosols in the Mexico City Metropolitan Area (MCMA) and surrounding region during two high fire periods in March 2006 have been evaluated using WRF-CHEM model. The model captured reasonably well the measurement-derived magnitude and temporal variation of the biomass burning organic aerosol (BBOA), and the simulated impacts of open fires on organic aerosol (OA) were consistent with many observation-based estimates. We did not detect significant effects of open fires and trash burning on surface O3 concentrations in the MCMA and surrounding region. In contrast, they had important influences on OA and elemental carbon (EC), increasing primary OA (POA) by ~60%, secondary OA (SOA) by ~22%, total OA (TOA = POA + SOA) by ~33%, and EC by ~22%, on both the local (urban) and regional scales. Although the emissions of trash burning are substantially lower than those from open fires, trash burning made slightly smaller but comparable contributions to OA as open fires did, and exerted an even higher influence on EC. Of the ~22% enhancement in SOA concentrations (equivalent to a ~15% increase in TOA) simulated, about two third was attributed to the open fires and one-third to the trash burning. On the annual basis and taking the biofuel use emissions into consideration, we estimated that open fires, trash burning and biofuel use together contributed about 60% to the loading of POA, 30% to SOA, and 25% to EC in both the MCMA and its surrounding region, of which the open fires and trash burning contributed about 35% to POA, 18% to SOA, and 15% to EC. The estimates of biomass burning impacts in this study may contain considerable uncertainties due to the uncertainties in their emission estimates in magnitude, temporal and spatial distribution, extrapolations and the nature of spot comparison. More observation and modeling studies are needed to accurately assess the impacts of biomass burning on tropospheric chemistry, regional and global air quality, and climate change.